Induced mutations in ASPARAGINE SYNTHETASE‐A2 reduce free asparagine concentration in the wheat grain. Issue 4 (16th June 2022) - Alarcón‐Reverte, Rocío; Xie, Yucong; Stromberger, John; Cotter, Jennifer D.; Mason, Richard Esten; Pearce, Stephen
Abstract: Acrylamide is a neurotoxin and probable carcinogen formed as a processing contaminant during baking and production of different foodstuffs, including bread products. The amino acid asparagine is the limiting substrate in the Maillard reaction that produces acrylamide, so developing wheat ( Triticum aestivum L.) cultivars with low free asparagine concentrations in the grain is a promising approach to reduce dietary acrylamide exposure. A candidate gene approach was used to identify chemically induced genetic variation in ASPARAGINE SYNTHETASE 2 ( ASN2 ) genes that exhibit a grain‐specific expression profile. In field trials, durum and common wheat lines carrying asn‐a2 null alleles exhibited reductions in free asparagine concentration in their grains of between 9 and 34% compared with wildtype sister lines. These plants showed no significant differences in spikelet number, grain size and weight, germination or baking quality traits. These nontransgenic variants can be deployed without regulatory oversight in elite wheat germplasm to reduce acrylamide‐forming potential with no negative effects on quality or agronomic performance. Core Ideas: Three wheat ASPARAGINE SYNTHETASE 2 knockout alleles were characterized in field experiments. Mutant alleles conferred significant reductions in grain free asparagine concentration. The alleles did not affect quality or agronomic traits.